Medical Care Utilization During 1 Year Prior to Death in Suicides Motivated by Physical Illnesses - Cho, Jaelim (The Korean Society for Preventive Medicine, 2013)
OBJECTIVES: Many epidemiological studies have suggested that a variety of medical illnesses are associated with suicide. Investigating the time-varying pattern of medical care utilization prior to death in suicides motivated by physical illnesses would be helpful for developing suicide prevention programs for patients with physical illnesses. METHODS: Suicides motivated by physical illnesses were identified by the investigator's note from the National Police Agency, which was linked to the data from the Health Insurance Review and Assessment. We investigated the time-varying patterns of medical care utilization during 1 year prior to suicide using repeated-measures data analysis after adjustment for age, gender, area of residence, and socioeconomic status. RESULTS: Among 1994 suicides for physical illness, 1893 (94.9%) suicides contacted any medical care services and 445 (22.3%) suicides contacted mental health care during 1 year prior to suicide. The number of medical care visits and individual medical expenditures increased as the date of suicide approached (p<0.001). The number of medical care visits for psychiatric disorders prior to suicide significantly increased only in 40- to 64-year-old men (p=0.002), women <40 years old (p=0.011) and women 40 to 64 years old (p=0.021) after adjustment for residence, socioeconomic status, and morbidity. CONCLUSIONS: Most of the suicides motivated by physical illnesses contacted medical care during 1 year prior to suicide, but many of them did not undergo psychiatric evaluation. This underscores the need for programs to provide psychosocial support to patients with physical illnesses.